Rozwiązane

Na teraz szybkoooo z gody dzięki !!!!
2. Sprawdź, czy poprawnie wykonano množenie i czy wyrażenie zostało poprawnie
uporządkowane.
-
a) (5x - 3y)(2x - 7y) = 10x² - 6xy - 35xy +21y² = 10x² - 41xy + 21y?
Tak /Nie
b) -(x + 4)(x - 3) = x2 - 4x -3x + 12 = x2 - 7x + 12
Tak /Nie



Odpowiedź :

Odpowiedź:

a) (5x - 3y)(2x - 7y) = 10x² - 35xy - 6xy + 21y² = 10x² - 41xy + 21y²

b) -(x + 4)(x - 3) = -(x² - 3x + 4x - 12) = -(x² + x - 12) = -x² - x + 12

Pozdrawiam ;)

Odpowiedź:

  1. a)(5x-3y)(2x-7y)=5x(2x-7y)-3y(2x-7y)=10x²-35xy-6xy-21y²=10x²-41xy-21y²
  2. -(x+4)(x-3)=-x(x-3)+4(x-3)=-x²+3x+4x-12=-x²+12x-12

Szczegółowe wyjaśnienie: